Lower Blood Pressure, Small‐Vessel Disease, and Apathy in Older Persons With Mild Cognitive Deficits. Issue 8 (30th April 2020) - Bertens, Anne Suzanne; Foster‐Dingley, Jessica C.; van der Grond, Jeroen; Moonen, Justine E.F.; van der Mast, Roos C.; Rius Ottenheim, Nathaly
Abstract : BACKGROUND: In older persons, both high and low blood pressure (BP) levels are associated with symptoms of apathy. Population characteristics, such as burden of cerebral small‐vessel disease (CSVD), may underlie these apparently contradictory findings. We aimed to explore, in older persons, whether the burden of CSVD affects the association between BP and apathy. DESIGN: Cross‐sectional study. SETTING: Primary care setting, the Netherlands. PARTICIPANTS: Community‐dwelling older persons (mean age = 80.7 years; SD = 4.1 years) with mild cognitive deficits and using antihypertensive treatment, participating in the baseline measurement of the magnetic resonance imaging substudy (n = 210) of the Discontinuation of Antihypertensive Treatment in the Elderly Study Leiden. MEASUREMENTS: During home visits, BP was measured in a standardized way and apathy was assessed with the Apathy Scale (range = 0‐42). Stratified linear regression analyses were performed according to the burden of CSVD. A higher burden of CSVD was defined as 2 or more points on a compound CSVD score (range = 0‐3 points), defined as presence of white matter hyperintensities (greater than median), any lacunar infarct, and/or two or more microbleeds. RESULTS: In the entire population, those with a lower systolic and those with a lower diastolic BP had more symptoms of apathy (β = −.35 [ P = .01] and β = −.66 [ P = .02], respectively). In older persons with a higher burden of CSVD (n = 50 [24%]), both lower systolic BP (β = −.64, P = .02) and lower diastolic BP (β = −1.6, P = .01) were associated with more symptoms of apathy, whereas no significant association was found between BP and symptoms of apathy in older persons with a lower burden of CSVD (n = 160). CONCLUSIONS: Particularly in older persons with a higher burden of CSVD, lower BP was associated with more symptoms of apathy. Adequate BP levels for optimal psychological functioning may vary across older populations with a different burden of CSVD. J Am Geriatr Soc 68:1811‐1817, 2020.